Water relations in physic nut according to climatic seasonality, in semiarid conditions - Rodrigues, Bruno Monteiro; Arcoverde, Gabriela Burle; Antonino, Antonio Celso Dantas; Santos, Mauro Guida (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to determine the effect of climatic seasonality on physic nut (Jatropha curcas), in field, under semiarid climate conditions. Stomatal conductance (gs), transpiration (E), soluble leaf carbohydrates (SLC), free amino acids (FAA) and total proteins (TP) were measured in leaves, in a commercial plantation in Northeast Brazil, during the summer and autumn. Plants showed high gs and E, as well as SLC, FAA and TP contents in the summer, which gradually decreased with the lower temperatures and photosynthetically active radiation during the autumn, despite the higher water availability. Even in conditions of adequate water availability, the combination of low temperatures and reduced light drastically decreased foliar metabolism.